To solve this equation, we need to subtract 6x to both sides of the equation, as a first step. Thus, we have:
![7x-6x=6x-6x-4\Rightarrow x=-4](https://img.qammunity.org/2023/formulas/mathematics/college/sueovi619ycgim04rosuqljrpbnr4orx9a.png)
![x=0-4\Rightarrow x=-4](https://img.qammunity.org/2023/formulas/mathematics/college/ho36cbds4fgf3hmpdo42laobgzssyzpafh.png)
In the subtraction of 7x and 6x, we subtract the coefficients (7 - 6 = 1). That is why we ended up with x. The result for 6x - 6x = 0, and we finally have -4 at the left side of the equation.
Therefore, the value for x is -4.
To check this equation, we can proceed as follows:
1. Substitute the value of x = -4 in the original equation:
7*(-4) = 6*(-4) - 4
Then
-28 = -24 - 4
-28 = -28 (that is true).
Hence, we have checked that x = -4 is the solution for the equation:
7x = 6x - 4.